Correction: Selective area growth of GaN nanowires and nanofins by molecular beam epitaxy on heteroepitaxial diamond (001) substrates. Issue 7 (20th March 2023) - Pantle, Florian; Becker, Fabian; Kraut, Max; Wörle, Simon; Hoffmann, Theresa; Artmeier, Sabrina; Stutzmann, Martin
Abstract : Correction for 'Selective area growth of GaN nanowires and nanofins by molecular beam epitaxy on heteroepitaxial diamond (001) substrates' by Florian Pantle et al., Nanoscale Adv., 2021, 3, 3835–3845, ; https://doi.org/10.1039/D1NA00221J .